Assessment of The Weight Loss Challenge (WLC) Initiative For Semarang City Health Office Employees - Daulati, Khoirina; Anggita, Gustiana Mega (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study employed the CIPP (Context, Input, Process, Product) evaluation model to assess the implementation of the Weight Loss Challenge (WLC) program for overweight and obese employees at the Semarang City Health Office. Data were gathered through documentation, interviews, and observation in a descriptive, qualitative manner. The steps of data reduction, data display, and conclusion drawing were followed by data analysis. According to the evaluation's findings, management fully supported the program's initial design, which was based on the real needs of the workforce. However, several technical and structural issues prevented the main goal of significant weight loss among participants from being accomplished during implementation. The program made effective use of internal resources without needing extra funding, but it was severely limited by the lack of science-based guidelines and restricted access to qualified instructors. Although the program was only run once a week, manual monitoring and a lack of feedback utilization resulted in a low level of responsiveness to necessary modifications. The program effectively raised participant motivation and helped create a healthier lifestyle culture in the workplace, despite the fact that the goal of reaching the ideal body weight based on the Body Mass Index was not reached.